Opportunities for motor stimulation in the home environment of children - da Silva W.R.* (2017)
Introduction: The environment in which the child is inserted and motor opportunities offered to this is essential for a good motor development. Objective: To analyze the relationship between the motor stimulation opportunities in the family environment and children's motor development of both sex. Methods: were evaluated 72 children, 33 boys and 39 girls with age of 38 to 42 months. The evaluation was conducted by Affordances in the Home Environment for Motor Development (AHEMD) and the Test of Gross Motor Development-2 (TGMD-2). Were used the tests Chi-square, Fisher exact test, t test for independent samples, Pearson correlation and multiple linear regression. Results: In general, the households have low opportunities for motor stimulation, and for households with boys the score is higher. The girls performed better in locomotor skills, while boys had higher scores on object control skills. It found a significant correlation to motricity materials and thick materials motor for boys and variety of stimulation, fine motor materials, motricity materials and motor stimulation for girls. For the boys the motor performance is explained by the available variables of fine and gross motor skills and for the girls by materials of motor stimulation, stimulation variety and materials of fine and gross motor skills. Conclusion: On the presented results we can conclude that the home environment is directly related to the motor development of girls and boys.